On temperature versus doping phase diagram of high critical temperature superconductors - Loktev, V.M.; Turkowski, V.M. (Condensed Matter Physics, 1998)
An attempt to describe the bell-shape dependence of the critical temperature
of high-Tc superconductors on the charge carrier density is made. It is
proposed to explain its linear increase in the region of small densities (underdoped
regime) by the role of the order parameter phase 2D fluctuations
which become less at this density growth. The critical temperature suppression
in the region of large carrier densities (overdoped regime) is connected
with the appearance (because of doping) of an essential damping
of long-wave bosons which, within the framework of the model proposed,
define the mechanism of indirect inter-fermion attraction. Зроблена спроба опису дзвоноподібної залежності критичної температури високотемпературних надпровідників від густини носіїв заряду. Пропонується пояснити її лінійне зростання в області малих густин
(недолегований режим) роллю 2D флуктуацій фази параметра порядку, які стають меншими при зростанні густини. Подавлення критичної температури в області великих густин носіїв (перелегований режим) пов’язаний з появою (завдяки легуванню) суттєвого затухання довгохвильових бозонів, які в рамках запропонованої моделі визначають механізм непрямого між-ферміонного притягання.